NALAR ‘IRFANI DALAM PENAFSIRAN: STUDI TAFSIR SUFI ‘ISYARI SAHL AL-TUSTARY - Azmin, Sirojul (UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
Al-Qur'an is a sacred doctrine for the Islamic community. It requires sincere effort and sound reasoning to delve into its interpretative meanings. In the epistemology of Islamic scholarship, three types of reasoning are known: bayani, Irfani, and burhani. Irfani reasoning comprises a set of epistemological principles that have garnered much debate, including strong opposition, with some figures vehemently prohibiting its use in interpreting the meanings of the Qur'an. This opposition aims to prevent the potential deviation from Islamic law, especially in matters of creed. Sahl al-Tustari is a renowned figure considered to be qualified in interpreting the Qur'an using Irfani or ishari reasoning. He is regarded as a moderate ishari figure, minimizing the likelihood of misinterpretation. The epistemology of Irfani reasoning has been practiced since the time of the Prophet Muhammad and has received direct approval from him. Using a descriptive-analytical method, this writing attempts to present and analyze the discourse on Sufi ishari commentary, along with the associated pros and cons.